2013
DOI: 10.1262/jrd.2012-017
|View full text |Cite
|
Sign up to set email alerts
|

Presence of a Temperature Gradient Among Genital Tract Portions and the Thermal Changes Within These Portions Over the Estrous Cycle in Beef Cows

Abstract: The aim of the present study was to describe the temperature of the different portions of the female genital tract and their relation to rectal temperature and to investigate the effect of steroid hormones profiles on these variables over the estrous cycle in cattle. Four nonpregnant Japanese Black cows were investigated daily over two successive estrous cycles using a digital thermometer with a long probe and rounded-end sensor to record the temperature of the rectum (RT), vagina (VT), cervix (CT), uterine bo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 25 publications
(14 citation statements)
references
References 59 publications
0
12
0
Order By: Relevance
“…Bovine body temperature is approximately 38.5°C, which increases under high ambient temperature (Sartori et al., 2002). The uterine temperature is typically higher than that of the rectum, vagina, or cervix (El‐Sheikh Ali et al., 2013; Gwazdauskas et al., 1973). An increased uterine temperature reduces blood flow into the uterus (Gwazdauskas et al., 1975; Roman‐Ponce et al., 1978), thus disturbing fetal development.…”
Section: Introductionmentioning
confidence: 99%
“…Bovine body temperature is approximately 38.5°C, which increases under high ambient temperature (Sartori et al., 2002). The uterine temperature is typically higher than that of the rectum, vagina, or cervix (El‐Sheikh Ali et al., 2013; Gwazdauskas et al., 1973). An increased uterine temperature reduces blood flow into the uterus (Gwazdauskas et al., 1975; Roman‐Ponce et al., 1978), thus disturbing fetal development.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, our team also monitored the body surface temperature of cows by measuring ankle temperature; however, its application is also unsuitable as it is affected by uncontrollable environmental factors (Kou et al 2017). The temperature correlation between rectum and vagina is 0.79, which is higher than that of uterine body, cervix, uterine angle and rectal temperature, and shows that long-term automatic monitoring VT to indicate core temperature is more scientific and reasonable than rectum (El-Sheikh Ali et al 2013). The real-time VT monitoring technique, based on sensor technology, is relatively new, and the automatically measured VT can serve as a strong indicator of bovine rectal temperature, since it is less affected by external factors (Collier et al 2006;Kendall et al 2007).…”
Section: Discussionmentioning
confidence: 99%
“…It has also been confirmed that the intravaginal temperature of bovines was elevated 0.4ºC at estrus [ 16 , 17 ]. Therefore, a temperature gradient of 39–41ºC, higher than body temperature (38–39ºC) [ 17 , 18 ], is formed in the reproductive tract of the estrus bovine, and thermotaxis may be involved in supporting the migration of fertilizing sperm. In this in vitro study, the thermotaxis of bull sperm toward the 1–2ºC higher temperature was confirmed.…”
Section: Discussionmentioning
confidence: 99%